Synthesis and Structural Study of the (N, N, N′, N′-Tetraethylethylenediamine)CdFe(CO)4 Dimer. (7th April 2014) - Kolb, Torsten; Arif, Atta M.; Ernst, Richard D.
Abstract : The new [(teeda)CdFe(CO)4 ]2 complex has been isolated from the reaction of[ ( NH 3 ) 2 CdFe(CO) 4 ] n with tetraethylethylenediamine. Unlike previous structural reports of ligand adducts of[ L 2 CdFe(CO) 4 ] x complexes, which have all been trimeric species composed of six-membered Cd3 Fe3 rings, the teeda complex crystallized as a dimer, analogous to [(2, 2-bpy)ZnFe(CO)4 ]2 . As in the zinc dimer, significant distortion arises from steric interactions between the axial carbonyl ligands on opposing iron centers. The complex sits on an inversion center, leading to two independent Cd–Fe distances, 2.7244(6) and 2.7433(6) Å, and crystallizes in the monoclinic space group P 21 / a with a = 14.8546(2) Å, b = 15.1647(3) Å, c = 15.5252(3) Å, β = 90.9517( 12 ) °, andD calc = 1.719 g/cm 3 at 150(1) K.